A Critical Study of Electioneering Strategies of Jamaat-e-Islami Pakistan and Its Impacts: 1970-2008 (Al-Qamar, 2021)
The Jamaat-e-Islami Pakistan (JIP) is one of the leading political parties of Pakistan deeply rooted in an Islamic ideology and it exercises deep influence in the political system. The arrest of Jamaat's leaders in 1950 forced the party to participate in active politics. This study focuses on Jamaat's election strategies of alliance politics, solo flight and boycott of elections and overall impacts upon JIP electoral politics. Jamaat-e-Islami enjoys great popularity across the country due to its Islamic ideology and social services, yet the party failed to translate its popularity into power of ballot, despite taking strong political stances. The party’s policy to attract the voters on religious and sociological issues has been analyzed in the light of Sociological Theory. The voting behavior to support the parties that match their religious, cultural and social needs, as prescribed in Sociological Theory, has been exposed with the historical study of the Jamaat's electoral politics. The primary data is collected by conducting interviews of political activists, and secondary sources that discussed the electoral politics in Pakistan. Election results have been assessed to know the causes of failure or success of Jamaat. The study applies both qualitative and quantitative methods to a scholarly study of electoral politics of Jamaat.
Keywords: Jamaat-e-Islami; Muttahida Majlis-e-Amal; Alliance Politics; Electoral Politics